Numerical and experimental study of transient conjugate heat transfer in helical closed-loop geothermal heat exchangers for application of thermal energy storage in backfilled mine stopes - Templeton, J.D. (John Wiley and Sons Ltd, 2020)
The geothermal potential available from deep underground mines has yet to be utilized. However, stope-coupled heat exchangers (SCHE) are aiming to take advantage of the unused low-grade geothermal energy. Backfilled stopes provide a unique opportunity to install nonlinear heat exchangers, as the geometry is not limited to the shape of a borehole. Helical pipes deliver superior fluid mixing and heat exchange compared to straight pipes, due to the effect of the secondary flow within the helical pipe. The helical closed-loop geothermal heat exchanger enables the backfilled stopes of the mine to be repurposed as thermal energy storage units. This article delves into the experimental results from a unique state-of-the-art laboratory scale helical closed-loop heat exchanger with varying thermophysical parameters. Additionally, a novel conjugate numerical model is developed and its results are validated against the base case of the experimental studies. Additionally, the numerical model is validated in a spatial-temporal sense with thermocouple data from the experimental rig. The numerical model is also applied to a helical SCHE situated within a backfilled stope for the first time. The results of the numerical model suggest that the pumping rate through the SCHE has a significant effect on the heat exchange rate and the overall energy transfer between the SCHE and the backfill. Additionally, the temperature contours from the numerical model suggest that a decreased pitch/helical diameter will increase the storage capacity of the helical SCHE. Overall, an average of 2.5 MW can be stored over the first 4 days of geothermal charging with the investigated full-scale SCHE, boasting a pseudo-steady-state storage rate of 1.7 MW. Â© 2020 John Wiley & Sons Ltd